1975
DOI: 10.1038/258577a0
|View full text |Cite
|
Sign up to set email alerts
|

Identification of two related pentapeptides from the brain with potent opiate agonist activity

Abstract: Enkephalin, a natural ligand for opiate receptors is composed of the pentapepides H-Tyr-Gly-Gly-Phe-Met-OH and H-Tyr-Gly-Gly-Phe-Leu-OH. The evidence is based on the determination of the amino acid sequence of natural enkephalin by the dansyl-Edman procedure and by mass spectrometry followed by synthesis and comparison of the natural and synthetic peptides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
904
1
44

Year Published

1977
1977
2007
2007

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 3,639 publications
(957 citation statements)
references
References 16 publications
8
904
1
44
Order By: Relevance
“…Met-and Leu-enkephalin first isolated from pig brain as endogenous ligands for opioid receptors [1 ], have later been shown to occur also in peripheral nervous tissue such as the plexus of the gastrointestinal tract of some species [2] and the bovine adrenal medulla [3,4]. Peptides probably identical with Metand Leu-enkephalin are also present in neuroblastoma X glioma hybrid cells 108CC15, as determined by 3 independent assays [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Met-and Leu-enkephalin first isolated from pig brain as endogenous ligands for opioid receptors [1 ], have later been shown to occur also in peripheral nervous tissue such as the plexus of the gastrointestinal tract of some species [2] and the bovine adrenal medulla [3,4]. Peptides probably identical with Metand Leu-enkephalin are also present in neuroblastoma X glioma hybrid cells 108CC15, as determined by 3 independent assays [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…In the literature, three fundamental 3D conformations have been characterized on these two endogenous opioid peptides using a variety of different methods°such°as°FT-IR°and°NMR°spectroscopy° [21,°22], molecular°modeling° [23][24][25],°and°mass°spectrometry [26,°27].°The°first°conformation°was°the°extended°con-formation, which can be stabilized by intermolecular hydrogen bonds. The second conformation is the ␤-turn folded form with two intramolecular hydrogen bonds; the°first°between°C¢O°(Tyr° [1]°and°N-H°(Gly° [3] and°the°second°between°C¢O°(Phe° [4]°and°N-H°(Tyr° [1]. The last conformation is the 3 10 -helix structure with an H°bond°between°C°ϭ°O°(Tyr° [1]°and°N-H°(Gly° [3]° [21, 28,°29].°These°conformations°have°been°characterized°in aqueous solutions, DMSO, and a mixture of these two solvents° [21].°Since°DMSO°has°a°similar°polarity°(P)°as acetonitrile (P ϭ 0.65 E°Al 2 O 3 for acetonitrile and P ϭ 0.62 E°Al 2 O 3 for DMSO), the resulting conformations are comparable with those characterized in the previous conditions.…”
Section: Molecular Modelingmentioning
confidence: 99%
“…The second conformation is the ␤-turn folded form with two intramolecular hydrogen bonds; the°first°between°C¢O°(Tyr° [1]°and°N-H°(Gly° [3] and°the°second°between°C¢O°(Phe° [4]°and°N-H°(Tyr° [1]. The last conformation is the 3 10 -helix structure with an H°bond°between°C°ϭ°O°(Tyr° [1]°and°N-H°(Gly° [3]° [21, 28,°29].°These°conformations°have°been°characterized°in aqueous solutions, DMSO, and a mixture of these two solvents° [21].°Since°DMSO°has°a°similar°polarity°(P)°as acetonitrile (P ϭ 0.65 E°Al 2 O 3 for acetonitrile and P ϭ 0.62 E°Al 2 O 3 for DMSO), the resulting conformations are comparable with those characterized in the previous conditions. In each case, the N-terminal function of these peptides is not involved in the hydrogen bonds; this observation leads us to suggest that the N primary labeling peptides would not dramatically influence conformations of the enkephalins.…”
Section: Molecular Modelingmentioning
confidence: 99%
“…15 This endogenous opioid pentapeptide was first discovered in the brain in the 1970s. 18,19 Investigations of structure-activity relationships showed that the Tyr 1 residue, the Phe 4 residue, and the Nterminal amino group are important for the opioid activity, and that the Gly at position 2 could be substituted with a D-amino acid 21 (for a review, see Ref. 20).…”
Section: Figurementioning
confidence: 99%